2020
DOI: 10.1111/jon.12729
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Treatment Delay Limits Outcome After Mechanical Thrombectomy: Stratification by Arrival Time and ASPECTS

Abstract: BACKGROUND AND PURPOSE: Mechanical thrombectomy (MT) has helped many patients achieve functional independence. The effect of time-to-treatment based in specific epochs and as related to Alberta Stroke Program Early CT Score (ASPECTS) has not been established. The goal of the study was to evaluate the association between last known normal (LKN)-to-puncture time and good functional outcome. METHODS: We conducted a retrospective cohort study of prospectively collected acute ischemic stroke patients undergoing MT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…In addition, as is consistent with our results, the delay from hospital arrival to puncture or from onset to reperfusion would worsen the outcome of mechanical thrombectomy for acute stroke (Bourcier et al, 2019;Kaesmacher et al, 2020;Snyder et al, 2020;Zhu et al, 2021). In this study, the model demonstrated the top 5 important variables, two of which are related to time, namely, time from onset to hospital, and time from onset to EVT.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, as is consistent with our results, the delay from hospital arrival to puncture or from onset to reperfusion would worsen the outcome of mechanical thrombectomy for acute stroke (Bourcier et al, 2019;Kaesmacher et al, 2020;Snyder et al, 2020;Zhu et al, 2021). In this study, the model demonstrated the top 5 important variables, two of which are related to time, namely, time from onset to hospital, and time from onset to EVT.…”
Section: Discussionsupporting
confidence: 89%
“…Endovascular therapy in addition to the medical treatment is now the standard of care for select patients who had a stroke caused by a large vessel occlusion in the anterior circulation. 1 The two main factors associated with a good outcome are time, namely the rapidity of the treatment, 2 and hemodynamic conditions. 3,4…”
mentioning
confidence: 99%
“…38,39 Recent research has shown that even a 15-minute delay in treatment is associated with a 10% decrease in the likelihood of good functional outcome. 40,41 In the past 2 decades, telestroke has become one of the most effective telemedicine applications by showing increased rates of tPA administration, reduced door-to-needle times, and decreased patient death and dependency. 42,43 Telerobotics refers to transmission of data through telecommunication systems to allow the active control of instruments by a remote physician located at a distance from the interventional suite.…”
Section: Teleroboticsmentioning
confidence: 99%